Interlimb asymmetries in football players with coordination impairments: implications for classification and training - Henríquez, M.; Sadarangani, K. P.; Cornejo, M. I.; Peña-González, I.; Yanci, J.; Reina, R. (International Journal of Sports Physiology and Performance, 2026)
Purpose: Football requires complex motor tasks to be performed under intermittent conditions, often involving asymmetrical movement. In footballers with cerebral palsy (CP), asymmetries are influenced by neuromuscular impairments, yet their role in performance differentiation across sport classes remains unclear. The objective of this study was to quantify interlimb differences and asymmetries in unilateral vertical and horizontal jump and change-of-direction (COD) performance among footballers with CP and to examine variations across different sport classes.